الاضطرابات السيكوسوماتية لدى عينة من عمال الصحة ذوو النمط السلوكي "أ" و"ب": دراسة ميدانية على الصحة "الطبيين وشبه الطبيين" - طراد، نفيسة Tarrad, Nafisah; أبى مولود، عبدالفتاح Aِِbi Mouloud, Abdulfattah (جامعة قاصدي مرباح - ورقلة, 2018)
The current study aimed at reveal psychosomatic disorders in a sample of the health team (medical and paramedical) with behavioral patterns (A and B) and knowledge of differences in sex, age and function. The present study was based the descriptive approach on a sample of (230 individuals) after the psychometric properties of the scales. The results of this study that: - Differences in the psychosomatic responses in the sample of the study in which the difference is due to the variable age and sex, except the function there are no differences between doctors and paramedics in the disorders of the psychosomatic. - There is a difference in the level of the psychosomatic disorders attributed to the behavioral pattern of the personality in favor of type B.
هدفت الدراسة الحالية إلى الكشف عن الاضطرابات السيكوسوماتية لدى عينة من الفريق الصحي (الطبي وشبه الطبي) ذوو الأنماط السلوكية (أ) و (ب) ومعرفة الفروق على مستوى الجنس والسن والوظيفة. حيث اعتمدت الدراسة على تطبيق المنهج الوصفي الارتباطي وذلك على عينة قصدية قوامها (230 فرد) بعدما تم التأكد من الخصائص السيكومترية للأدوات، وخلصت نتائج هذه الدراسة إلى: -تختلف الاستجابات السيكوسوماتية لدى عينة الدراسة يعزى فيها الاختلاف إلى متغير السن والجنس، فيما عدا الوظيفة لا توجد فروق بين الأطباء وشبه الطبيين في الاضطرابات السيكوسوماتية. - يوجد اختلاف في مستوى الاضطرابات السيكوسوماتية تعزى للنمط السلوكي للشخصية لصالح ذوو النمط (ب).
Keywords: الشخصية -- الاضطرابات السيكوسوماتية -- النمط السلوكي (أ) -- النمط السلوكي (ب) -- المستشفيات -- ولاية ورقلة -- الجزائر